Answer:
Explanation:
When there is a ( + ) in front of an expression in parentheses, there is no need to change the sign.
That means the expression remains the same.
Just remove the parentheses
Collect like terms
⇒
Calculate the difference
Hope I helped!
Best regards!!
9514 1404 393
1 -3i
For purposes of addition or subtraction, the i can be treated as though it were a variable. Terms can be collected in the usual way.
4 +2i +(-3 -5i) = 4 +2i -3 -5i
= (4 -3) +i(2 -5) = 1 -3i
5.7m questions
7.5m answers